Behavioral economics and healthy behaviors key concepts and current research - Hanoch, Yaniv; Barnes, Andrew J. (Abingdon, Oxon Routledge, Taylor & Francis Group, 2017)
"The book opens with an overview of the core theoretical concepts, after which each chapter assesses how behavioral economic research and practice can inform public policy across a range of health issues. Including chapters on tobacco, alcohol and drug use, physical activity, dietary intake, cancer screening and sexual health, the book integrates the key insights from the field to both developed and developing nations."--Provided by publisher.
Acknowledgements -- Background material -- Introduction / Yaniv Hanoch, Andrew J. Barnes, and Thomas Rice -- A brief overview of behavioral economic / Thomas Rice, Yaniv Hanoch, and Andrew J. Barnes -- Shaping health behaviour -- The behavioral economics of tobacco products : innovations in laboratory methods to inform regulatory science / Warren K. Bickel, Lara N. Moody, Sarah E. Snider, Alexandra M. Mellis, Jeffrey S. Stein, and Amanda J. Quisenberry -- Understanding alcohol and other drug use via behavioral economics : review and clinical applications / Michael Amlung, Joshua Gray, and James MacKillop -- Behavioral economic tools for promotion of physical activity / Tammy Leonard and Kerem Shuval -- Using behavioral economics to improve dietary intake : alternatives to regulation, bans, and taxation / Marie A. Bragg and Brian Elbel -- Detecting and managing disease -- Improving medication adherence with behavioral economics / Steven E. Meredith and Nancy M. Petry -- Integrating principles from behavioral economics into patient navigation programs targeting cancer screening / Yan Li, Fernando A. Wilson, Roberto Villarreal, and Josâe A. Pagâan -- Behavioral economics and HIV : a review of existing studies and potential future research areas / Sebastian Linnemayr -- Behavioral economics and health behaviors among the poor : findings from developing country populations / Jill Luoto -- The role of providers, insurers, and government -- Applications of behavioral economics to clinical quality improvement / Daniella Meeker and Jason N. Doctor -- Using behavioral economics to improve people's decisions about purchasing health insurance / Andrew J. Barnes, Thomas Rice, and Yaniv Hanoch -- The role of government : how behavioral economics can inform policies to improve health behaviors / Aditi P. Sen and Richard G. Frank -- About the editors and authors -- Index.
Includes bibliographical references and index.
Keywords: Economics -- Psychological aspects; Medical economics